When quality today affects service needs tomorrow - Kari Eika (University of Oslo, Department of Economics, 2004)
Quality in the human services has long term effects. Reduced quality of service now increases the service recipients' future service needs and other social costs. This paper shows that such effects should be considered when a government designs contracts with a for-profit service provider. If the contract relies on verifiable information only, short contract periods fail to give the provider proper incentives to internalize future effects of quality. Long term contracts are problematic if the effects of quality are not over time indicated by verifiable measures. Relational contracts seem more robust to changes in the model's informational assumptions and rely on trust to deal with holdups. Long term quality effects matter for the relative merits of intergrated provision and contracting out, and may create adverse quality incentives if a for-profit provider has market power.
Keywords: D69; 330; human services; quality of service; for-profit; Öffentliche Dienstleistung; Outsourcing; Dienstleistungsqualität; Vertragstheorie